The Influence Of Human Resource Development, Leadership, And Work Discipline On The Performance Of ASN Employees At The Regional Office Of The Ministry Of Religion Of North Sumatra Province - Adelia Sarumaha; Kholilul Kholik; Wilchan Robain (Jurnal Fokus Manajemen, 2026)
This study aimed to examine the effects of human resource development, leadership, and work discipline on the performance of civil servant employees at the Regional Office of the Ministry of Religious Affairs of North Sumatra Province. The study used an associative quantitative approach by collecting primary data through questionnaires. The population of this study consisted of all civil servant employees at the Regional Office of the Ministry of Religious Affairs of North Sumatra Province, totaling 247 employees. The sample size was 71 respondents, determined using the Slovin formula, with purposive sampling as the sampling technique. This study was conducted in 2025. The data obtained from the questionnaires were processed using SPSS 24.0 with multiple linear regression analysis. The results showed that human resource development had a regression coefficient of 0.306, a t value of 3.220, and a significance value of 0.002; leadership had a regression coefficient of 0.369, a t value of 3.905, and a significance value of 0.000; and work discipline had a regression coefficient of 0.288, a t value of 2.987, and a significance value of 0.004. The F value was 236.992 with a significance value of 0.000. These results indicated that human resource development, leadership, and work discipline partially and simultaneously had positive and significant effects on the performance of civil servant employees at the Regional Office of the Ministry of Religious Affairs of North Sumatra Province. Leadership was the most dominant variable affecting employee performance, with the highest standardized coefficient beta value of 0.382. Employee performance was explained by human resource development, leadership, and work discipline by 91.8 percent, indicating a very strong relationship.